Metastatic urothelial carcinoma in multiple appendicular muscles of a cat - Eduardo M Hernández; Pedro J Ginel; Beatriz Blanco; Yolanda Millán; Maria T Jiménez; Elena Mozos (Journal of Feline Medicine and Surgery Open Reports)
Case summary A 13-year-old male castrated domestic shorthair cat presented with a 2-month history of progressive lameness, poor appetite and constipation. Physical examination revealed palpable lesions in muscles of several extremities. Ultrasound examination confirmed the presence of round lesions with a hypo- or anechoic centre within the muscles. These lesions were characterised by an anechoic, occasionally trabeculated, central area surrounded by a hyperechoic band with heterogeneous echotexture. In total, seven lesions affecting six appendicular muscles were detected in different evolution stages, as suggested by their sizes and ultrasonographic features. Fine-needle aspiration of the muscle lesions revealed nests and isolated pleomorphic large neoplastic cells consistent with a carcinoma (vs sarcoma) and one mass was surgically removed. The histological and immunohistochemical studies confirmed a diagnosis of metastatic urothelial carcinoma. Although this neoplasia typically originates from the urothelium of the urinary bladder or renal pelvis, the primary tumour could not be detected in repeated abdominal ultrasound examinations. The cat was euthanased and further evaluations were declined by the author. Relevance and novel information Urothelial carcinoma is a rare and highly aggressive neoplasia in the cat. While metastasis to regional lymph nodes and lungs are common in cats and dogs, to the authors’ knowledge, there have been no reports of metastasis to multiple appendicular muscles in cats. This clinical presentation should be considered in the differential diagnoses of multiple nodular or cystic lesions affecting long muscles in cats.